2010
DOI: 10.1371/journal.pone.0009096
|View full text |Cite|
|
Sign up to set email alerts
|

Ambient Air Pollution and the Progression of Atherosclerosis in Adults

Abstract: BackgroundCross-sectional studies suggest an association between exposure to ambient air pollution and atherosclerosis. We investigated the association between outdoor air quality and progression of subclinical atherosclerosis (common carotid artery intima-media thickness, CIMT).Methodology/Principal FindingsWe examined data from five double-blind randomized trials that assessed effects of various treatments on the change in CIMT. The trials were conducted in the Los Angeles area. Spatial models and land-use d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
192
3
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 230 publications
(212 citation statements)
references
References 38 publications
(86 reference statements)
13
192
3
4
Order By: Relevance
“…coronary calcium and ankle brachial index (Diez Roux et al 2008). A recent study demonstrates that long-term PM exposure is not only related to the degree, but also to a faster progression rate of atherosclerosis (Kunzli et al 2010). Along with this epidemiological evidence, experimental research also established a link between exposure to PM and the development of atherosclerosis.…”
Section: Chronic Pm Exposure and Atherosclerosismentioning
confidence: 93%
“…coronary calcium and ankle brachial index (Diez Roux et al 2008). A recent study demonstrates that long-term PM exposure is not only related to the degree, but also to a faster progression rate of atherosclerosis (Kunzli et al 2010). Along with this epidemiological evidence, experimental research also established a link between exposure to PM and the development of atherosclerosis.…”
Section: Chronic Pm Exposure and Atherosclerosismentioning
confidence: 93%
“…These biomarkers have been consistently linked to subsequent cardiovascular disease and death. Long-term exposure has also been associated with preclinical markers of atherosclerosis (Künzli et al, 2005) and with progression (Künzli et al, 2010) of this pathology of high relevance to cardiovascular diseases. A series of studies from the German Heinz Nixdorf Recall Study has confirmed associations between various markers of atherosclerosis, including intima media thickness and coronary artery calcification, and the long-term average PM 2.5 concentration and proximity to traffic in Europe (Bauer et al, 2010;Hoffmann et al, 2006Hoffmann et al, , 2007.…”
Section: Critical Data Gapsmentioning
confidence: 99%
“…Still, considering that laboratory rats have the advantages of moderate body type, easy breeding, more offspring and low costs, using SD rats to develop AS is a simple and noninvasive method for generating an AS model. Epidemiological studies have shown that an important relationship exists between AS and exposure to particulate air pollution 1,25,26) . Moreover, Araujo et al reported that ultrafine particle (diameter<100 nm) exposures have a higher proatherogenic potential than fine particle exposures 27) .…”
Section: Discussionmentioning
confidence: 99%
“…Data from abundance studies well indicate that air particulate pollution is directly linked to the adverse cardiovascular outcomes in the general population 1) . Epidemiological studies have indicated that individuals suffering from cardiovascular disease have increased susceptibility to particulate matter and other air pollutants 2,3) .…”
Section: Damage Multi-walled Carbon Nanotubesmentioning
confidence: 99%